Toward the unveiling of HIV-1 dynamics: Involvement of monocytes/macrophages in HIV-1 infection - Sukegawa, Sayaka; Takeuchi, Hiroaki (Frontiers in Virology, 2022)
HIV-1 targets the monocyte/macrophage lineage and CD4+ T cells for its replication. The efficiency of infection, replication and cell-to-cell spread differs between these cell types. These differences are caused by various factors such as viral tropism, viral proteins, host factors, and cell proliferation. However, the precise mechanisms of how macrophages influence HIV-1 infection have not been fully elucidated. Macrophages are long-lived cells susceptible to infection predominantly with R5-tropic strains of HIV-1. Although co-receptor use switches from CCR5 to CXCR4 in up to 50% of patients during AIDS progression, R5-tropic strains remain predominant in the remaining patients. Compared to HIV-1-infected T cells, infected macrophages are less susceptible to HIV-induced cytopathic effects and survive for more than a few weeks. Efforts to cure HIV-1 may be thwarted by the existence of reservoir cells that cannot be targeted by ART. Resting CD4+ T lymphocytes are thought to be the primary reservoir cells, but recent studies demonstrated that monocyte/macrophage lineage cells may also act as viral reservoirs. This review will focus on the impact of monocytes/macrophages during HIV-1 replication, the establishment of the reservoirs, and recent approaches toward HIV-1 eradication by specifically targeting monocyte/macrophage lineage cells.